Spirulina platensis como mimetizador da restrição calórica em ratos - Konrath, Greici (2011)
Caloric restriction (CR) can delay or prevent diseases related to age in different species, varying from yeast to primates. Although the application of this diet in humans remain uncertain, the proportion of the benefits of CR could add more healthy years to average life than even the cure of cancer or heart diseases. As a few people would be willing to maintain a life style under CR, the search for substances that can mimic their beneficial effects, health and longevity seem to be very important nowadays. The use of cianobacteria Spirulina platensis has shown to increase life time of models like yeast and rodents because of its functional properties. The present work objectified to verify platensis the mimetizator potential of the microseaweed Spirulina in the beneficial effect of the caloric restriction. For that, 30 adult rats Wistar were submitted to treatments: control (C), caloric restriction (CR) and Spirulina platensis (Sp). For treatment Spirulina platensis the standard rat chow was increased with 1.5 g of Spirulina platensis/Kg chow; for group caloric restriction the reduction of 30 % in diet was made compared to control group. The parameters evaluated were: weight, glucose, TBARS and lipid profile, through measures of total cholesterol, HDL, LDL and TGA. The results obtained show that the body mass of group CR was kept, thus groups C and Sp increased significantly (p<0.001). The levels of TGA remained in groups CR and Sp and increased in group C (p=0.0039). HDL cholesterol showed no significant difference (p>0.05). The values of LDL increased in group C (p= 0.0075) and in groups CR and Sp, remained. Total cholesterol reduced significantly in group RC only (p<0.05). The indexes of TBARS reduced in groups CR and Sp compared with the control group. The levels of glucose did not changed when compared to pre and post treatments to different groups. The results of the beneficial effect in the levels of TGA, lipidic cholesterol LDL,lipoperoxidation (TBARS) and maintenance of the weight for the platensis use of the Spirulina in the process of aging of rats, in this study, indicate that this cianobactéria can be used as a mimetizator functionary of the caloric restriction